Nutrition and Eating Patterns among Preschoolers in Gaza Strip - Kanoa, Basil J.; Hamed, Amine T.; Zabut, Baker M. (Pakistan Journal of Nutrition, 2011)
The study aim to assess the nutrition and eating patterns among Preschool Age Children (PSC) in Gaza Strip. The study design was cross sectional study carried-out in the five governorates of Gaza Strip. The study population was preschool children that were chosen from eligible Kindergartens (KG). Official approval to conduct the research study was obtained from the ministry of education and higher education and consent form from parents to participate mother and coming to the KG was obtained. Data were collected through face to face interviews with the children’s mothers. The questionnaire was designed to include two parts: sociodemographic part and food frequency of animal and plant product. The results showed that about 44% of the surveyed children were given milk once daily, while 11.2% of them did not receive it at all. About 32.9% of the surveyed children were give fish once per week while 8.8% did not receive it at all. With exception to meat either fresh, frozen or canned there is no statistical significance relationship between frequencies of eating liver, fish, eggs and milk in relation to governorates. The percentage of the surveyed children were given vegetables and fruits once daily were (71.1%, 53.1%) respectively. It was found that 7% are given fruits each two weeks or more. With exception to vegetables, there is statistical significance relationship between bread, rice, macaroni, fruits, legumes, sweets and fruit juices in relation to governorates.